Analysis of the Relationship Between Physical Activity and Physical Fitness Among Grade X Nursing Assistant Students - Muhamad Taufiq hidayatullah; Eko Hariyanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to examine the relationship between physical activity, physical fitness level, and physical readiness among Grade X Nursing Assistant students at SMKN 11 Malang in facing learning demands and fieldwork practice. This study used a quantitative, descriptive correlational approach, with all Grade X students in the program as subjects. Physical fitness was measured using the Indonesian Student Fitness Test (TKSI) for students aged 16-19, while physical activity was measured using the Global Physical Activity Questionnaire (GPAQ). Descriptive results indicate that students' physical fitness is still predominantly in the moderate to poor category in several components, particularly cardiorespiratory endurance, reaction time, and agility. Meanwhile, students' physical activity is in the moderate to high category, but it is still accompanied by relatively long sitting durations. These findings suggest that unstructured daily physical activity does not necessarily align with optimal physical fitness. Therefore, more innovative physical education (PE) learning, targeted training programs, and reinforcement of active lifestyle habits are needed to continuously improve students' physical readiness.